Xanthos, East Basilica, Corpus of Mosaics of Turkey, Volume 1 - RAYNAUD, Marie-Patricia
Chronological and stylistical study of the mosaics decorating the East Basilica in Xanthos, Early Byzantine Period.
p. 119-122, 2 plans, 10 ill. coul.Éditeur : Bursa, Uludağ UniversityColloque : 2007, Gaziantep
Keywords: Bibliographie par pays, région ou ensemble géographique; Datation; Église (Xanthos, TUR) de l'Est; Style, stylistique (étude); Xanthos-Letôon